Size-fractionated nonpolar organic compounds of traffic aerosol emissions in a highway tunnel. (15th January 2022) - Li, Xinling; Feng, Jialiang; Li, Yingjie; Zhao, Pengcheng; Pan, Xiaoxuan; Huang, Zhen
Abstract: Size-fractionated aerosol samples (PM0.25, PM0.25-1, PM1-2.5, and PM2.5-10 ) were collected in a highway tunnel in Shanghai, China. The concentrations of nonpolar organic compounds (NPOCs), i.e., n -alkanes, polycyclic aromatic hydrocarbons (PAHs) and hopanes in the aerosol samples at the tunnel inlet and outlet, emission factors (EFs) of individual NPOCs in PM10, and EFs of size-fractionated individual NPOCs were analyzed comprehensively. NPOC concentrations in this tunnel were lower than the earlier tunnel results, which might be attributed to the tunnel configuration effect on the pollution dilution along the tunnel, in addition to the improvement of engine technology and fuel quality during past decades. n -Alkane homologs for C14 –C35 exhibited a smooth hump-like distribution pattern with the most abundance at C22 and 1–2 carbon number shifts of Cmax in comparison to those in other tunnels due to different fleet and fuel compositions. The most abundant PAHs from diesel (e.g., Nap, Phe, Flu and Pyr) and gasoline (e.g., BghiF, BbkF, BeP, DBA and BghiP) vehicle emissions presented concentration increases of 1.8–5.8 times from the tunnel inlet to outlet. The individual n -alkane and PAH distributions exhibited obvious size dependence, while it was expected that the relative abundances and homolog distributions of hopanes were very similar for different size stages. Several diagnostic ratios, e.g., fossil/plant n -alkanes and LMW/HMW PAHs, were evidently size dependent, indicating different sources of size-fractionated n -alkanes and PAHs. Graphical abstract: Image 1 Highlights: Size-fractionated aerosol samplers were collected in a highway tunnel. Nonpolar organic compound concentrations in our tunnel were lower than earlier tunnel results. n -Alkane and PAH distributions exhibited obvious size dependence.